Frequency of Odontogenic Tumors in Zahedan-Iran from 2000 to 2010 - Hamideh Kadeh; Shirin Saravani; Tahereh Nosratzehi; Feizorrahman Rasulizadeh (Mashhad University of Medical Sciences, 2012)
Introduction: Odontogenic tumors constitute an important aspect of oral and maxillofacial pathology. Frequency of odontogenic tumors varies in different societies but no study has been done in Zahedan so far. The purpose of this study was to achieve the sex, location and age distribution of odontogenic tumors and frequency of each one in a period of ten years.Materials & Methods: In this study, documents in archive of maxillofacial pathology department of Zahedan dental school, Khatamolanbia, Tamin ejtemaei Hospital and private laboratories were reviewed from 2000 to 2010. Data about age, sex, location of tumors and relation with impacted tooth were extracted and were submitted in the forms.Results: In this study, among the 1125 cases of the oromaxillofacial lesions, 50 cases of odontogenic tumors were found. Among the different tumors, keratocyst odontogenic tumor (KOT) was the most common odontogenic tumor (48%), followed by ameloblastoma and odontoma with frequency of 24% and 12%, respectively. There were no cases of malignancy. The incidence of these lesions was 52% in women and 48% in men. The most common location of tumors was posterior of mandible and tumors were more frequent in the third decade of life. In 12 cases, the lesions were accompanied by impacted teeth.Conclusion: In this study the most frequent tumors were KOT, Ameloblastoma and odontoma respectively.